Municipal healthcare providers’ perceptions of reasons for frequent and unplanned hospital admissions among home-dwelling older adults: a Norwegian focus group study - Jill-Marit Moholt; Cathrine Arntzen; Audhild Høyem; Bodil H. Blix (BMC Geriatrics)
Abstract Background In healthcare policies and research, patients who utilise substantial healthcare services receive significant attention. Persons who are frequently admitted to hospitals are often termed ‘frequent users of hospital services’. Understanding how front-line healthcare providers in municipal healthcare services perceive these patients’ healthcare needs is crucial for developing adequate and integrated care across healthcare levels. This study aimed to examine how healthcare providers within municipal healthcare services recognise and describe the healthcare needs of home-dwelling older adults with frequent and unplanned admissions to somatic hospitals. A central aspect of the study was to explore what healthcare providers identify as the reasons for these hospital admissions. Methods This qualitative study employed an exploratory design. We conducted six focus group discussions involving a total of 26 healthcare providers from home-based services and institutional short-term wards in four Norwegian municipalities. The data were analysed using a six-step reflexive thematic analysis. Results The participants’ perceptions of the needs and reasons for unplanned hospital admissions among home-dwelling older frequent service users included aspects at both the individual and structural levels. At the individual level, healthcare providers highlighted patient characteristics such as the severity of illness, reduced functional ability, living situation, and unmet psychosocial needs. At the structural level, participants emphasised system issues that could intensify the need for hospital admissions, such as in-hospital care failing to address complexity before discharge, hasty discharges with insufficient information sharing, and a lack of essential and comprehensive municipal healthcare services, such as home-based night care. Conclusions This study demonstrates that healthcare needs and reasons for unplanned hospital admissions among older, frequent users are multifaceted and influenced by both individual and structural factors. Based on our findings, we recommend that healthcare policies aimed at reducing unplanned and potentially avoidable hospital admissions address structural-level issues. This includes ensuring access to essential and comprehensive municipal healthcare services and fostering integrated care through collaboration and dialogue between hospitals and municipal healthcare services.